Interaction of State, Law and Religious Organizations in Pre- Revolutionary Russia - BATOROV, Sergei Evdokimovich; BATOROVA, Tatjana Prokopjevna; MALAKSHINOVA, Nadezhda Shagzhievna; NAMZHILON, Auna Batomunkuevna; TSYBIKOV, Bator Bulatovich (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
The article studies some issues of cooperation between the state and religious denominations in prerevolutionary Russia. The subject of our research is urgent due to social changes in modern Russia, which increase interest in religion. Therefore, the state needs to make changes in strategy of relations with religious associations taking into account the historical experience of these relations. The aim of the research is to study historical development of the church-state relations and features, the knowledge of which will help to regulate relations between the state and church in the modern period. The results of the study have shown that the state plays the leading role, and the church has become the inseparable part of the state system.